Impact of Absenteeism and Organizational Conflict on Employee Performance in Enugu State Civil Service, 2010–2019 - Umeokafor, Chibuike Chris (Indonesian Development of Economics and Administration Journal, 2025)
The lack of employee performance, efficiency, and service delivery in Enugu State Civil Service has been perpetuated by persistent absenteeism and unresolved organizational conflict to raise questions about weak motivation, poor management practices, and deteriorating productivity in the public sector between 2010 and 2019. This descriptive work has been carried out in Enugu State, Nigeria and has outlined the historical, geographic, economic and administrative environment in which the Enugu State Civil Service is based. The study population is the civil service, which has 10,100 employees working in 20 ministries. Using Yamane formula, 385 workers were randomly picked out of 10 ministries. Primary sources such as interviews with key officials and secondary sources were used to collect data. Reliability and validity were upheld in the study, and the content analysis of qualitative data was used to analyze absenteeism, organizational conflict, and employee performance. The results show that absenteeism and organizational conflict are the most critical issues that reduce the performance of employees within the Enugu State Civil Service. Job insecurity, lack of motivation, delayed promotions, and poor working conditions are what cause absenteeism, thus interfering with productivity and service delivery. Competition and limited resources further diminish teamwork and morale when managed improperly, which leads to organizational conflict. Nonetheless, it has been indicated that when conflict is managed effectively and integratively, cooperation, innovation, and performance can be improved. The paper highlights the importance of sound human resource management, enhanced employee morale, and active conflict-management approaches to enhance output and service delivery.